DEVELOPMENT OF STUDENTS' ENTREPRENEURIAL SPIRIT THROUGH DEMOCRATIC LEADERSHIP AT VOCATIONAL SCHOOLS - Suharry; Hasan Maksum; Yulastri, Asmar; Wawan Purwanto; Yuliana (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The development of students' entrepreneurial spirit in Vocational High Schools (SMK) through democratic leadership has become a topic that has received attention in the world of education. Leadership, entrepreneurship, and education theories play a crucial role in shaping a supportive, inclusive, and effective learning environment in developing students' entrepreneurial skills. Recent research shows that the implementation of democratic leadership in vocational schools has a positive impact on student motivation, courage, collaboration, and involvement in entrepreneurial activities. The integration of these theories is a strong foundation in designing relevant and effective learning programs for the development of students' entrepreneurial spirit. Through a holistic and sustainable approach, SMK has the potential to create a young generation that is resilient, innovative, and ready to compete in the competitive business world.